Database and Expert Systems Applications 21st International Conference, DEXA 2010, Bilbao, Spain, August 30 - September 3, 2010, Proceedings, Part II - García Bringas, Pablo; Hameurlain, Abdelkader; Quirchmayr, Gerald (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2010)
st We welcome you to the proceedings of the 21 International Conference on Database and Expert Systems Applications held in Bilbao. With information and database s- tems being a central topic of computer science, it was to be expected that the integ- tion of knowledge, information and data is today contributing to the again rapidly increasing attractiveness of this field for researchers and practitioners. Since its foundation in 1990, DEXA has been an annual international conference, located in Europe, which showcases state-of-the-art research activities in these areas. DEXA 2010 continued this tradition and provided a forum for presenting and discu- ing research results in the area of database and intelligent systems and advanced - search topics, applications and practically relevant issues related to these areas. It offered attendees the opportunity to extensively discuss requirements, problems, and solutions in the field in the pleasant atmosphere of the city of Bilbao, which is known for its driving industriousness, its top cultural venues and its rich and inspiring he- tage and lifestyle. The University of Deusto with its great educational and research traditions, and the hospitality which the university and the city are so famous for, set the stage for this year's DEXA conference. This volume contains the papers selected for presentation at the DEXA conference.